2013
DOI: 10.1002/pola.26529
|View full text |Cite
|
Sign up to set email alerts
|

ESI, APCI, and MALDI tandem mass spectrometry of poly(methyl acrylate)s: A comparison study for the structural characterization of polymers synthesized via CRP techniques and the software application to analyze MS/MS data

Abstract: Research in polymer science and engineering is moving from classical methodologies to advanced analytical strategies in which mass spectrometry (MS)-based techniques play a crucial role. The molecular complexity of polymers requires new characterization tools and approaches to elucidate the detailed structural information. In this contribution, a comparison study of poly(methyl acrylate)s (PMA) using different tandem mass spectrometry techniques (ESI, APCI, and MALDI MS/MS) is reported to provide insights into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…For CID fragmentation experiments, argon was used as the collision gas at a pressure of 1.5 × 10 −6 Torr and the collision energy amounted to 20 keV . MALDI spectra were run “neat” in a dithranol (Sigma‐Aldrich, St Louis, MO, USA) matrix.…”
Section: Methodsmentioning
confidence: 99%
“…For CID fragmentation experiments, argon was used as the collision gas at a pressure of 1.5 × 10 −6 Torr and the collision energy amounted to 20 keV . MALDI spectra were run “neat” in a dithranol (Sigma‐Aldrich, St Louis, MO, USA) matrix.…”
Section: Methodsmentioning
confidence: 99%
“…Although numerous fragmentation techniques exist and are applied to synthetic polymers, the most widely used technique is CAD, which is closely related to PSD and in- For example, aromatic side chain based polymers such as PS has numerous different applications due to their importance in life science, and poly(2-vinylpyridine) (P2VP), for instance, in membranes as well as in batteries, and features a similar structure to PS, with only a slightly different side chain [20]. Furthermore, poly(acrylate)s are also important for contact lenses, membranes [21] as well as nanoparticles for energy storage [22]; MS/MS studies have been reported on poly(methyl acrylate) (PMA) [20,23], poly(methyl methacrylate) (PMMA) [20,24,25], poly(t-butyl methacrylate) (PtBMA), poly(t-butyl acrylate) PtBA and poly(n-butyl acrylate) (PnBA) [20,26]. Other important polymers that have been investigated include poly(vinyl acetate) (PVA) [20,27], poly(methacrylic acid) (PMAA) and poly(acrylic acid) (PAA) [20,28], polyesters [29][30][31][32][33][34], poly(lactide) (PLA) [35][36][37][38], poly(ethylene oxide) (PEO) [20,39,40], and poly(oxazoline)s [41][42][43][44], all of which show remarkable promise in biodegradable and biocompatible materials [21,[45][46][47].…”
Section: Ms/ms Techniquesmentioning
confidence: 99%
“…The use of organic matrices in MALDI-MS can, however, result in an inhomogeneous distribution of analyte crystals, leading to poor reproducibility [10,11]. In addition, polymers subjected to highpower UV-laser irradiation in MALDI-MS can undergo undesirable fragmentation [12][13][14]. Consequently, the complicated array of fragment ions will result in higher MS background noise and loss of MS resolution, making it more difficult to determine the full chemical structure and molecular weight of the polymer.…”
Section: Introductionmentioning
confidence: 96%